2000
DOI: 10.1080/026404100750017823
|View full text |Cite
|
Sign up to set email alerts
|

Stress reactivity after maximal exercise: The effect of manipulated performance feedback in endurance athletes

Abstract: This study was designed to assess the effect of performance feedback on stress reactivity after recovery from maximal exercise. Forty competitive athletes were recruited to complete a maximal exercise test. Performance feedback was manipulated after the exercise test to give four groups: (1) high performance, (2) low performance, (3) accurate feedback and (4) no exercise control. Cardiovascular reactivity was assessed during psychological stress. The results indicate that accurate feedback participants experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…This study therefore provides support for this supposition, and although the results are not unexpected, they are novel. Previous research concerning performance feedback and high-intensity exercise has largely focussed on knowledge of results or manipulated performance feedback given postexercise, or performance feedback given during an incremental test 14 15. In these studies, the provision of correct performance feedback led to improved performance15 and reduced stress reactivity 14.…”
Section: Discussionmentioning
confidence: 99%
“…This study therefore provides support for this supposition, and although the results are not unexpected, they are novel. Previous research concerning performance feedback and high-intensity exercise has largely focussed on knowledge of results or manipulated performance feedback given postexercise, or performance feedback given during an incremental test 14 15. In these studies, the provision of correct performance feedback led to improved performance15 and reduced stress reactivity 14.…”
Section: Discussionmentioning
confidence: 99%
“…Given that positive exercise performance feedback has been shown to result in a greater attenuated BP response to stress than neutral or negative feedback (Bartholomew 2000), it is important to minimise experimenter bias by ensuring that the researcher who administers the stressors is blind to the preceding treatment.…”
Section: Introductionmentioning
confidence: 99%
“…While behaviors like consuming high-fat meals appear to enhance cardiovascular reactivity, other behaviors, such as exercise, have been found to reduce cardiovascular reactivity. Numerous investigators have shown that acute bouts of exercise can decrease cardiovascular reactivity if done at a high intensity (Alderman, Arent, Landers, & Rogers, 2007;Bartholomew, 2000;Hamer, Taylor, & Steptoe, 2006). When exercise doses were greater than 30 min at 50% VO 2max, a meta-analysis has shown large effects on the reductions of cardiovascular reactivity (Hamer et al, 2006).…”
mentioning
confidence: 99%